Chassis inventory management at U.S. container ports:modelling and case study. Issue 18 (17th September 2017) - Ng, ManWo; Talley, Wayne K.
Abstract : Recently, marine container chassis have emerged at the forefront of container port operations in the United States, after shipping lines stopped providing chassis as part of their service. With the operation and management responsibilities transferred to new parties, chassis dislocation has been a major problem across the United States. To ensure chassis availability, one response has been the creation of so-called neutral chassis pools, introducing new challenges for container port operations. This paper presents a mathematical model that can be used to objectively support the management and planning of neutral chassis pools. An empirical case study is provided to illustrate the model.